How educational mobile games can help children to learn more about Malay culture / Abdullah Abdul Rahman Awang @ Awang Khalid - Awang @ Awang Khalid, Abdullah Abdul Rahman (2023)
This study explores the potential of educational mobile games in promoting children's learning about Malay culture. The primary purpose of this research is to explore ideas in educational games that can help children learn about Malay customs and traditions and identify the Malay culture's history and roots. Through a qualitative research approach, semi-structured interviews were conducted with parents of kids who use mobile phones and are interested in Malay culture to gather their perceptions and experiences regarding using educational mobile games for cultural learning. Thematic analysis was applied to the interview data, uncovering key themes and patterns. The findings reveal that educational mobile games can be practical tools for introducing children to Malay culture. These games provide interactive and immersive learning experiences, fostering cultural pride, identity, and understanding. Themes include the positive impact on understanding Malay culture through educational mobile games, challenges and the importance of parental Involvement and Guidance. The study also highlights the challenges in accessing quality resources and emphasizes the significance of parental involvement and guidance in enhancing children's cultural learning experiences. The findings contribute to a new interactive educational game design by using a new method of learning to acknowledge children about the Malay culture that had been aside by the young generation nowadays. Underscoring the importance of incorporating culturally relevant content and promoting parental engagement. Overall, educational mobile games promise to foster children's knowledge and appreciation of Malay culture while providing an engaging and enjoyable learning experience. It is hoped that the study can contribute to the improvement of cultural knowledge to upcoming generation.